Association between plain water intake and risk of hypertension: longitudinal analyses from the China Health and Nutrition Survey - Shizhen Li; Xun Xiao; Xiangyu Zhang (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to investigate the prospective association between plain water intake and the risk of hypertension based on a longitudinal cohort study in China.MethodsLogistic regression analyses were performed to investigate the association between plain water intake and hypertension. Restricted cubic spline model was use to evaluate non-linear relationship between plain water intake and hypertension. Subgroup analyses and interaction tests were conducted based on age, gender, residence site, educational level and tea consumption.ResultsA total of 3,823 participants (46.5% male) with a mean age of 46.8 years from the China Health and Nutrition Survey (CHNS) were assessed and divided into 4 groups based on plain water intake. There was a decreasing trend of hypertension risk as plain water intake increased. Logistic regression analyses indicated that participants consuming plain water ≥6 cups/day (1 cup ≈ 240 mL) had significantly lower risk of hypertension compared to those consuming ≤1 cup/day, even after adjustments for covariates. Restricted cubic spline curve revealed that participants consuming about 6-8 cups/day were at lower risk for developing hypertension. In subgroup analyses, the results were generally consistent with the main findings in participants who aged less than 60 years, who were male, who attained higher education and who were low tea consumers.ConclusionOur findings suggested that there might be a favorable effect of plain water intake on preventing hypertension in a large cohort of Chinese adults from the general population. Drinking adequate amounts of plain water (about 6-8 cups/day) may reduce the risk of hypertension, particularly in the selected population. Further interventional studies are required to investigate the potential effect of increasing plain water intake on blood pressure regulation.